Environmental Impact of Dairy Effluent - Khalid Iqbal, Ansari Ahmed, Yakub Ansari, Ansari Rashid, Abdullah Khan (International Journal of Advanced Science and Technology, 2020)
Livestock industry plays an important role in socio-economic life of the world. It is a rich and major source of high quality foods such as milk, eggs and meat. Demand for milk and milk products caused rapidly growth of dairy industries in most countries of the world. Consequently, the amount of waste material and wastewater generated and discharged from these industries has also increased. The main object of the paper is to review present research on dairy wastewater. The different, origin, categories, and general indicators of dairy wastewater are described. The dairy industry consumes large volumes of milk and the major waste material from processing is the water. The water far from the milk can contain considerable amounts of minerals and organic milk products. Also cleaning of plant, leads to caustic wastewater. This review article discusses the impact of wastewater released in the environment.